2020
DOI: 10.3390/ijerph17051579
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Fipronil Treatment Induces Hyperactivity in Female Mice

Abstract: Fipronil is an insecticide widely used for veterinary and agricultural purposes. While its insecticidal properties mostly rely on its high affinity antagonistic activity on insect γ aminobutyric acid (GABA) receptors, fipronil and its main metabolite fipronil sulfone nevertheless display non-negligible affinity for mammalian GABA A receptor. As several environmental toxicants have been shown to raise the risk of developing various neurodegenerative disorders, the aim of this study was to evaluate whether long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…As mentioned earlier, FIP and fipronil sulfone (FIP main metabolite) act as inhibitors of insect GABA receptors and prevent GABA binding to its receptor, blocking the inhibitory function of GABA in the central nervous system and, thus, leading, at low doses, to neuronal hyperexcitation and, at high doses, to the paralysis and death of insects (Koslowski et al 2020). Fipronil has a notably higher affinity for insect GABA receptors than for mammalian GABA receptors (Hainzl et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned earlier, FIP and fipronil sulfone (FIP main metabolite) act as inhibitors of insect GABA receptors and prevent GABA binding to its receptor, blocking the inhibitory function of GABA in the central nervous system and, thus, leading, at low doses, to neuronal hyperexcitation and, at high doses, to the paralysis and death of insects (Koslowski et al 2020). Fipronil has a notably higher affinity for insect GABA receptors than for mammalian GABA receptors (Hainzl et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Both FIP and fipronil sulfone are able to cross the blood-brain barrier in rats and mice (Hainzl et al 1998;Cravedi et al 2013). A recent study, evaluating the long-term low dose administration of FIP in mice and its relation to cognitive deficiencies showed that a 48-week-FIP treatment leads to behavioural perturbations, indicating an accumulative effect of sustained exposure to low doses of FIP (Koslowski et al 2020). In the present study, no significant symptoms specific to the nervous system were observed over the whole experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the LC 50 for fipronil in African clawed frog ( X. laevis ) tadpoles was 850 μg/L; the LC 50 s for bluegill sunfish ( Lepomis macrochirus ) and rainbow trout ( Oncorhynchus mykiss ) were 85 and 248 μg/L, respectively (Wang et al, 2019). An oral LD 50 for fipronil in rats was 97 mg/kg, but a dermal LD 50 was 2 g/kg in the same species (Koslowski et al, 2020). An acute dermal LD 50 in rabbits was 354 mg/kg.…”
Section: Introductionmentioning
confidence: 99%
“…An acute dermal LD 50 in rabbits was 354 mg/kg. Five‐day dietary LC 50 s for bobwhite quail and mallard ducks were 49 mg/kg and 5 g/kg, respectively (Koslowski et al, 2020). LC 50 s for midges ( Chironomus dilutus ), mysid shrimp ( Neomysis americana ), grass shrimp ( Palaemonetes pugio ), black flies ( Simulium vittatum ), and Daphnia were 0.082, 0.14, 0.32, 0.18–0.31, and 190 μg/L, respectively (CDC, 2005; Maeda et al, 2021).…”
Section: Introductionmentioning
confidence: 99%